Pengaruh Persepsi tentang Peran Gender Feminin terhadap Munculnya Perilaku Seksual yang Sifatnya Menghargai atau Tidak Menghargai Pasangannya - Delvita Minanga dan Muslimah Zahro Romas (LPPM Universitas Proklamasi 45, 2011)
Objective of this research is to find the influence of male's perception on feminine gender role toward their tendency to behave sexually. Behaving sexually could be respect or disrespect their mates. It was about 70 students from a private university, aged 15-18 years old, single, participated in this study. The independent variabel was male's perception on feminine gender role, whls the dependent variable was male's tendency to behave sexually. The item validation analysis for the Feminine Gender Role Perception Scale found that the r( was ranged .243-.S62, whilst the rn for the Behavior Tendency on Sexual Behavior Scale was ranged .237-.6S5. The hypothesis analysis using the regression analysis revealed that the male's perception on feminine gender role influenced male's sexual behavior (F (1,69) = 10.489, p<.05). Contribution of the independent variable toward the dependent variable was more likely low (13.4%) albeit significant. Several research weakness and recommendations for future research were discussed.